Building a Madrasah Positive Image: How are The Strategies? - Mahmud, Muchammad Eka; Torres, Joel Mayo; Fadlilah, Fadlilah (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This research aimed to investigate the strategy of madrasah in cultivating a positive image of the institution. This research used a subjective or qualitative research method with a phenomenological approach. The research was conducted in MTSN Samarinda by collecting, presenting, and confirming data. The researcher used data collection techniques of observation, interviews, and documentation. The research subjects were the vice principal of MTSN Samarinda and the students. The researcher also observed the school's social media platforms and documents, such as the school admission brochure. As for the data analysis technique, the researcher used the theories of Miles, Huberman, and Saldana to analyze data. The data credibility and validity were also tested using triangulation. The research results show that (1) MTs Negeri Samarinda builds the image of the institution by identifying the needs of the community, especially prospective students, by creating a quality Madrasah institution in various programs as well as prioritizing Islamic values, (2) MTs Negeri Samarinda also maximizes student activity programs both in terms of academic and non-academic aspects which include various extracurricular activities, clean Friday programs implemented from the adiwiyata program and tahfidzul Qur'an class programs, (3) The school also maximizes all programs by publishing them on social media platforms such as Instagram, YouTube, and websites. This study highlights the importance of madrasah’s strategies in cultivating a positive image of an institution.